Performance Evaluation of Different Backoff Algorithms in IEEE 802.15.4 using Double Sensing - Md. Mohibur Rahaman; Mohammad Khairul Islam; Kazi Ashrafuzzaman; Mohammad Sanaullah Chowdhury (Institute of Advanced Engineering and Science, 2017)
The IEEE 802.15.4 is the standard for Low Rate Wireless Personal Area network (LR-WPAN). It is widely used in many application areas. The standard uses Slotted CSMA/CA mechanism in its contention access period (CAP) for the beacon enabled mode. The protocol has two modes - single sensing (SS) and double sensing (DS). The protocol also adopts a binary exponential backoff (BEB) algorithm. In this paper, we explore the saturation throughput, delay and energy consumption of this standard with double sensing (DS) using the existing BEB algorithm. We also investigate three other backoff schemes - exponential increase exponential decrease (EIED), exponential increase linear decrease (EILD) and exponential increase multiplicative decrease (EIMD). From simulation results, it is found that the EIED, EILD, EIMD perform better than the BEB for higher loads. It shows that the EIED, EILD, EIMD have better throughput and lower delay than the BEB. The EIED outperforms the other schemes in terms of throughput, delay and energy for the higher loads.